2021
DOI: 10.1186/s12866-021-02259-2
|View full text |Cite
|
Sign up to set email alerts
|

Composition and diversity of gut microbiota in Pomacea canaliculata in sexes and between developmental stages

Abstract: Background The apple snail, Pomacea canaliculata, is one of the world’s 100 worst invasive alien species and vector of some pathogens relevant to human health. Methods On account of the importance of gut microbiota to the host animals, we compared the communities of the intestinal microbiota from P. canaliculata collected at different developmental stages (juvenile and adult) and different sexes by using high-throughput sequencing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 68 publications
5
24
0
Order By: Relevance
“…To some extent, this is consistent with the view that tadpoles have a diverse diet (Bennett, 1992;Karasov, 1992). The functional differences of intestinal microbiota at different developmental stages might be attributed to the changes of diet and development (Chen, Cui, et al, 2021;Chen, Li, et al, 2021;Moya & Ferrer, 2016). For example, the relative abundance of Clostridiaceae was more enriched in the forelimb bud stage, the infections with bacteria of the genus Sarcina (family Clostridiaceae) in human and animal were associated with gastric dilation and emphysematous gastritis (Owens et al, 2021), consistent with the functional prediction that human disease were more enriched in the forelimb bud stage.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To some extent, this is consistent with the view that tadpoles have a diverse diet (Bennett, 1992;Karasov, 1992). The functional differences of intestinal microbiota at different developmental stages might be attributed to the changes of diet and development (Chen, Cui, et al, 2021;Chen, Li, et al, 2021;Moya & Ferrer, 2016). For example, the relative abundance of Clostridiaceae was more enriched in the forelimb bud stage, the infections with bacteria of the genus Sarcina (family Clostridiaceae) in human and animal were associated with gastric dilation and emphysematous gastritis (Owens et al, 2021), consistent with the functional prediction that human disease were more enriched in the forelimb bud stage.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, it is necessary to expand intestinal microbiota studies with more species. Hynobius maoershanensis primarily lives in the surrounding area of the alpine swamp and the vegetation nearby consists primarily of hemlock forest and mountaintop dwarf forest (Chen, Cui, et al, 2021;Chen, Li, et al, 2021;Jiang & Jiang, 2006). The larvae of H. maoershanensis live an aquatic life, whereas the adults live amphibiously.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence indicated that the gut microbiota was a dynamic system that was inevitably influenced by multiple intrinsic and extrinsic factors, including diet, age, and sex environment (32)(33)(34). Generally, the physiological fluctuations of gut microbiota caused by the above-mentioned factors cannot affect intestinal normal function and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…P. canaliculata in winter were generally sampled under the soil by fishing net because snails overwinter were buried in the bottom sediments. All experimental individuals were wiped by 75% ethanol three times, followed by rinsing twice in distilled water to sanitize the surface prior to dissection and removing the shell from each snail (Chen et al, 2021 ). Coiled gut contents were extracted carefully to avoid rupturing the gut wall.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of the microbiota was diverse among the different gut sections. Significant differences were found in the structure of gut microbiota among female, male, and juvenile groups, suggesting the gut microbiota of P. canaliculata has been affected by the developmental stages (Chen et al, 2021 ). Zhou et al ( 2022 ) investigated difference of gut microbiota between P. canaliculata and native snail Cipangopaludina chinensis .…”
Section: Introductionmentioning
confidence: 99%